PENGEMBANGAN BUKU SAKU SEBAGAI MEDIA PROMOSI KESEHATAN TENTANG CACINGAN YANG DITULARKAN MELALUI TANAH PADA SISWA KELAS IV SDN 01 KROMENGAN KABUPATEN MALANG - Andi Ahmad; Sapto Adi; Rara Warih Gayatri (Universitas Negeri Malang, 2017)
Abstract: The prevalence of soil transmitted helminth at SDN 01 Kromengan reached 48 % and higher when it’s compared to other schools in Malang Regency. Soil transmitted helminth prevalence of fourth grade students reached 61.25% and became the highest of the other classes. According to Andini (2015), it is advisable to provide a posters as a health promotion media. Since it only has a little material coverage and can’t be taken anywhere, while the facilities and infrastructure is not sufficient for other media then it is necessary to develop the appropriate media that is a pocket book. The development model used is a procedural model with adopted steps according to Sugiyono (2016). The analysis technique used is quantitative analysis technique that is descriptive analysis and qualitative analysis technique. The result of this research and development is a pocket book titled